The ArmarX Statechart Concept: Graphical Programing of Robot Behavior - Wächter, Mirko; Ottenhaus, Simon; Kröhnert, Manfred; Vahrenkamp, Nikolaus; Asfour, Tamim (Frontiers in Robotics and AI, 2016)
Programming sophisticated robots such as service robots or humanoids is still a complex endeavor. Although programming robotic applications requires specialist knowledge, a robot software environment should support convenient development while maintaining full flexibility needed when realizing challenging robotics tasks. In addition, several desirable properties should be fulfilled, such as robustness, reusability of existing programs, and skill transfer between robots. In this work, we introduce the ArmarX statechart concept, which is used for describing control and data flow of robot programs. This event-driven statechart approach of ArmarX helps realizing important features such as increased robustness through distributed program execution, convenient programming through graphical user interfaces, and versatility by interweaving dynamic statechart structure with custom user-code. We show that using hierarchical and distributed statecharts increases reusability, allows skill transfer between robots, and hides complexity in robot programming by splitting robot behavior into control flow and functionality.